2015
DOI: 10.4103/1673-5374.167767
|View full text |Cite
|
Sign up to set email alerts
|

The longitudinal epineural incision and complete nerve transection method for modeling sciatic nerve injury

Abstract: Injury severity, operative technique and nerve regeneration are important factors to consider when constructing a model of peripheral nerve injury. Here, we present a novel peripheral nerve injury model and compare it with the complete sciatic nerve transection method. In the experimental group, under a microscope, a 3-mm longitudinal incision was made in the epineurium of the sciatic nerve to reveal the nerve fibers, which were then transected. The small, longitudinal incision in the epineurium was then sutur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…Peripheral nerve injury is common in clinical cases and affects the patients' quality of life severely (1)(2)(3). Thus, investigating the molecular mechanisms underlying the peripheral nerve regeneration for the development of medical therapies is critical.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Peripheral nerve injury is common in clinical cases and affects the patients' quality of life severely (1)(2)(3). Thus, investigating the molecular mechanisms underlying the peripheral nerve regeneration for the development of medical therapies is critical.…”
mentioning
confidence: 99%
“…In recent years, microRNAs (miRNAs) 3 are a class of small noncoding RNAs that have emerged, as key post-transcriptional regulators in a majority of the eukaryotic cells (6,7). In animals, miRNAs bind to partially complementary sites in mRNAs, leading to translational repression and mRNA deadenylation and degradation (8 -10).…”
mentioning
confidence: 99%
“…The dedifferentiation, proliferation, migration, and myelin clearance of Schwann cells, a vast majority of cells in the injured distal nerve stump, are evidently associated with successful nerve regeneration (Bosse, 2012). Research has shown that blocking Schwann cell proliferation and migration might attenuate axonal regeneration in transected nerves (Chen et al, 2005). Therefore, clarifying the mechanisms underlying the modulation of Schwann cell behavior and finding promising molecules for nerve injury therapy are of great importance.…”
Section: Discussionmentioning
confidence: 99%